Application of femoral nerve block combined with modified swelling anesthesia in high ligation and stripping of great saphenous vein - Chen, Xiaobin; Liu, Zhenwen; Zhou, Binbin; Fan, Zuyou; Zhao, Hu; Lin, Chen (Frontiers in Surgery, 2023)
Background: To analyze and explore the clinical efficacy of ultrasusionguided femoral nerve block combined with modified swelling anesthetic solution in high ligation and stripping of the great saphenous vein. Methods: A total of 90 patients who were scheduled to undergo high ligation and stripping of great saphenous vein due to varicose veins of lower extremity were selected and randomly divided into group A (femoral nerve block combined with modified swelling anesthesia), group B (swelling anesthesia alone) and group C (epidural anesthesia) by random number method, with 30 cases in each group. The preoperative and postoperative serum CRP levels, operation duration, intraoperative blood loss, postoperative hospital stay, total hospitalization costs, postoperative VAS score, preoperative and postoperative VCSS score, intraoperative mean arterial pressure and heart rate, postoperative related complications, and patients' satisfaction with diagnosis and treatment were compared among the three groups. Results: There were no significant differences in operation duration, intraoperative blood loss, postoperative complications, and preoperative and postoperative VCSS scores among the three groups (P>0.05). The postoperative length of hospital stay, postoperative VAS score and total hospitalization cost in groups A and B were lower than those in group C, and the postoperative length of hospital stay and postoperative VAS score in group A were more significant (P<0.05). Compared with group B, the fluctuation range of intraoperative mean arterial pressure and heart rate, and postoperative serum CRP level in groups A and C were lower, and the postoperative serum CRP level in group A was more significantly decreased (P<0.05). The results showed that the number of postoperative complications in group A was lower than that in the other two groups (P<0.05), and the postoperative complications in the three groups were effectively relieved after symptomatic treatment (dressing change, anti-infection, taking circulatory drugs, etc.). The satisfaction of patients in group A was significantly higher than that in groups B and C (P<0.05). Conclusions: Ultrasusionguided femoral nerve block combined with modified swelling anesthetic solution applied in high saphenous vein ligation and exhalation can significantly improve postoperative inflammatory stress response of patients, effectively ensure the safety and reliability of surgical progress.